Internalization of the Values of Religious Moderation Through Gus Dur's Cultural Preaching in the Anshor Youth Movement in Totokaton Village, Central Lampung - Amri Zainul Ikhsan; Hasyim Asy’ari; M.Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study examines the internalization of religious moderation values through Gus Dur's cultural da'wah in Gerakan Pemuda Ansor (GP Ansor) of Toto Katon Village, Punggur District, Central Lampung. The phenomena of radicalism and intolerance pose serious threats to the pluralistic nation, making religious moderation an imperative that must be upheld. Using a qualitative descriptive approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation. This research addresses three main issues: (1) how Gus Dur's cultural da'wah is understood and practiced by GP Ansor members; (2) how the internalization of religious moderation values takes place within the community; and (3) what factors support or hinder this process. The findings reveal that GP Ansor has successfully internalized religious moderation values through structured cadre education, participation in local cultural traditions, and exemplary personal conduct. The implementation of Gus Dur's cultural da'wah through local traditions, personal modeling, and accessible humorous language proved effective and aligned with the community's existing cultural practices. The internalization process follows three stages: moral knowing, moral feeling, and moral action. Supporting factors include NU leader support, structured cadre programs, strong local religious traditions, and coordination with higher-level GP Ansor. Inhibiting factors encompass radical social media influence, limited understanding among some members, and resource constraints. This study affirms that Gus Dur's da'wah approach remains highly relevant and effective in shaping moderate character among grassroots youth